2013
DOI: 10.1103/physrevlett.111.190603
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Response in the Driven Lattice Lorentz Gas

Abstract: We determine the nonlinear time-dependent response of a tracer on a lattice with randomly distributed hard obstacles as a force is switched on. The calculation is exact to first order in the obstacle density and holds for arbitrarily large forces. Whereas, on the impurity-free lattice, the nonlinear drift velocity in the stationary state is analytic in the driving force, interactions with impurities introduce logarithmic contributions beyond the linear regime. The long-time decay of the velocity toward the ste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
73
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 40 publications
12
73
0
Order By: Relevance
“…(14) and (15), and using the definition (10), one can explicitly obtain the TP velocity in the dilute limit, for arbitrary choice of jump probabilities and time scales τ, τ * . Notice that the comparison between the expression for V (F ) obtained in the dilute limit for unconfined geometries [44], following a computation analogous to that reported here, and the analytical result of [41], revealed that the decoupling approximation is indeed exact at lowest order in ρ, for arbitrary values of the time scales τ, τ * . We claim that this statement also holds for confined geometries.…”
Section: Linearized Solution In the Dilute Regimementioning
confidence: 99%
See 2 more Smart Citations
“…(14) and (15), and using the definition (10), one can explicitly obtain the TP velocity in the dilute limit, for arbitrary choice of jump probabilities and time scales τ, τ * . Notice that the comparison between the expression for V (F ) obtained in the dilute limit for unconfined geometries [44], following a computation analogous to that reported here, and the analytical result of [41], revealed that the decoupling approximation is indeed exact at lowest order in ρ, for arbitrary values of the time scales τ, τ * . We claim that this statement also holds for confined geometries.…”
Section: Linearized Solution In the Dilute Regimementioning
confidence: 99%
“…Recently, the behavior of V (F ) beyond the linear regime in lattice gas models has received great attention, triggered by the observation of the striking phenomenon of negative differential mobility (NDM), namely a nonmonotonic dependence of the TP velocity on the applied force [39][40][41][42][43][44][45]. Upon a gradual increase of the force F , the velocity grows linearly, as prescribed by the linear response, then approaches a maximal value and further decreases with an increase of F .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The γ = 0 case corresponds to the driven lattice Lorentz gas and is known to show negative response irrespective of the choice of p, q [6,16,19]. The study of this system was started in the context of diffusion in random media with focus on the phase transition to a zero-current regime [19,20,21,22].…”
Section: Modelmentioning
confidence: 99%
“…Specific examples follow in the next sections. For broader physics background on the models and for previous work we also refer to [13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%